Analysis Of Payroll And Wage Accounting Systems In Internal Control at PT. Daria Dharma Pratama Oil Palm Plantation (Case Study of Sibak Village, Ipuh District, Mukomuko Regency) - Ahmad Sumarlan; Hafizh misbach yezet (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The formulation of the problem in this study is how is the implementation of the payroll and wage accounting system at PT. Daria Dharma Pratama . The aim is to find out how the implementation of the payroll and wage accounting system at PT. Daria Dharma Pratama . This research includes descriptive research. This study aims to determine the payroll and wage accounting internal control system at PT. Daria Dharma Pratama , where the internal control system has indicators such as organizational structure, authorization system, healthy practices, and capability of employees. The data used are primary data and secondary data. Primary data in the form of data obtained directly from HRD and company assistants. Secondary data was obtained to complement the primary data, namely: History of company development and organizational structure of PT. Daria Dharma Pratama , company activities and company payroll and wage systems. Data analysis techniques were carried out by systematically arranging interview guidelines, field notes, and library data to gain knowledge from data of PT Daria Dharma Pratama , then formulates it descriptively, and at last processes the data. The results of the analysis show that there is a good segregation of duties so that employees are more focused on one job and manipulation of data on employee attendance lists because it only contains time attendance, as well as a lack of monitoring of employee attendance in the field, this shows the weaknesses that occur in the company's system Internal control over payroll and remuneration is not good. Keywords : Accounting System, Payroll and Wages, Internal Control System The formulation of the problem in this study is how is the implementation of the payroll and wage accounting system at PT. Daria Dharma Pratama . The aim is to find out how the implementation of the payroll and wage accounting system at PT. Daria Dharma Pratama . This research includes descriptive research. This study aims to determine the payroll and wage accounting internal control system at PT. Daria Dharma Pratama , where the internal control system has indicators such as organizational structure, authorization system, healthy practices, and capability of employees. The data used are primary data and secondary data. Primary data in the form of data obtained directly from HRD and company assistants. Secondary data was obtained to complement the primary data, namely: History of company development and organizational structure of PT. Daria Dharma Pratama , company activities and company payroll and wage systems. Data analysis techniques were carried out by systematically arranging interview guidelines, field notes, and library data to gain knowledge from data of PT Daria Dharma Pratama , then formulates it descriptively, and at last processes the data. The results of the analysis show that there is a good segregation of duties so that employees are more focused on one job and manipulation of data on employee attendance lists because it only contains time attendance, as well as a lack of monitoring of employee attendance in the field, this shows the weaknesses that occur in the company's system Internal control over payroll and remuneration is not good. Keywords : Accounting System, Payroll and Wages, Internal Control System